2019
DOI: 10.3897/mycokeys.52.32335
|View full text |Cite
|
Sign up to set email alerts
|

How useful is the current species recognition concept for the determination of true morels? Insights from the Czech Republic

Abstract: The phylogentic diversity of the genus Morchella has only been sporadically studied in Central Europe. In this study, a molecular taxonomic revision of the Morchella species of the Czech Republic was performed using available fungarium specimens, fresh collections, and axenic cultures. Molecular phylogenetic analyses based on either ITS or five-locus (ITS, LSU, RPB1, RPB2, and EF-1α) sequencing and the application of principles of the genealogical concordance phylogenetic species recognition (GCPSR) have revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…In our study, the nuclear ITS region showed the highest intraspecific and interspecific divergences (0.00062 and 0.1347, respectively), as well as the highest species identification (44.44%) among the single candidate DNA barcodes. These results were largely consistent with previous studies on Morchella species [ 25 , 41 ]. Thus, we suggested that the ITS marker should be incorporated into the core barcode marker for Morchella species.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the nuclear ITS region showed the highest intraspecific and interspecific divergences (0.00062 and 0.1347, respectively), as well as the highest species identification (44.44%) among the single candidate DNA barcodes. These results were largely consistent with previous studies on Morchella species [ 25 , 41 ]. Thus, we suggested that the ITS marker should be incorporated into the core barcode marker for Morchella species.…”
Section: Discussionsupporting
confidence: 93%
“…In Morchella, the pitfalls of single-method approaches are exemplified by another recent study by Petrželová and Sochor (2019), focusing on molecular phylogenetics. While the authors of this study are correct to point out that many problems in the genus stem from the application of different methods of analysis and in some cases over-splitting, some of their proposals are unlikely to help.…”
Section: The Pitfalls Of Single-methods Approaches In Taxonomymentioning
confidence: 99%
“…While molecular phylogenetics have since clarified the species richness debate, early phylogenetic assessments were faced with the daunting task of matching the numerous phylogenetic clades (phylospecies) inferred through molecular tools to the several dozens of Linnaean binomials available, many of which type material were not available for or, if it existed, were too old to yield useful DNA data. To tackle this problem, the system of informal Mel/Mes designators for each phylospecies was introduced by Taşkın et al (2010) andO'Donnell et al (2011), and widely adopted in subsequent studies (Du et al 2012a, b;Pildain et al 2014;Richard et al 2015;Loizides et al 2016;Petrželová and Sochor 2019). This system, which used the prefix "Mel" for the /Elata clade and "Mes" for the /Esculenta clade followed by a serial number for each species, did not intend to replace binomial nomenclature (as falsely assumed by Phanpadith et al 2019), but was introduced as a temporary solution until the phylogenetic identity of early published binomials could be clarified.…”
Section: The System Of Binomial Nomenclature and The Mel/mes Designatorsmentioning
confidence: 99%
See 2 more Smart Citations